Studies on the extremo-lipase produced by the halotolerant Oceanobacillus iheyensis strain QCS - Noura Sh. A. Hagaggi (Novel Research in Microbiology Journal)
In the current work, different studies were carried out on the lipase enzyme produced by the halotolerant Oceanobacillus iheyensis strain QCS, with an expectation to be an important candidate in the industrial applications. Lipase of strain QCS was halo-alkali-thermo-detergent-solvent stable. Maximum production of lipase was obtained after 72 h of incubation, at 40oC and pH 8 and 9 in a medium containing 25 % (w/v) NaCl and 1% (v/v) olive oil as a lipid substrate. This lipase was partially purified, highest lipase activity was obtained in 80% ammonium sulfate saturation, and in fraction eight of the Sephadex G-200 gel filtration chromatography. Lipase displayed wide spectrum of activity within a broad range of conditions including salinity, temperature and pH, it was optimally active at 25% (w/v) NaCl, 40°C and pH 8 and 9, respectively. The effect of many metal ions, detergents and organic solvents on the activity of lipase was evaluated. Interestingly, lipase was able to retain the majority of its activity in the presence of Ni2+, Mg2+, Oxi and Fairy detergents, ethyl acetate, dimethyl formamide and toluene, respectively. Overall, as the lipase from O. iheyensis strain QCS has a number of interesting properties especially its stability at extreme conditions; it could be used as a potential promising candidate for detergents industry, and as a biocatalyst in low water enzymatic processes.